Effects of intraspecific diversity on survivorship, growth, and recruitment of the eastern oyster across sites. Issue 6 (1st June 2016) - Hanley, Torrance C.; Hughes, A. Randall; Williams, Bethany; Garland, Hanna; Kimbro, David L.
Abstract: Intraspecific diversity, particularly of foundation species, can significantly affect population, community, and ecosystem processes. Examining how genetic diversity relates to demographic traits provides a key mechanistic link from genotypic and phenotypic variation of taxa with complex life histories to their population dynamics. We conducted a field experiment to assess how two metrics of intraspecific diversity (cohort diversity, the number of independent juvenile cohorts created from different adult source populations, and genetic relatedness, genetic similarity among individuals within and across cohorts) affect the survivorship, growth, and recruitment of the foundation species Crassostrea virginica . To assess the effects of both cohort diversity and genetic relatedness on oyster demographic traits under different environmental conditions, we manipulated juvenile oyster diversity and predator exposure (presence/absence of a cage) at two sites differing in resource availability and predation intensity. Differences in predation pressure between sites overwhelmingly determined post‐settlement survivorship of oysters. However, in the absence of predation (i.e., cage treatment), one or both metrics of intraspecific diversity, in addition to site, influenced long‐term survivorship, growth, and recruitment. While both cohort diversity and genetic relatedness were negatively associated with long‐term survivorship, genetic relatedness alone showed a positive association with growth and cohort diversity alone showed a positive association with recruitment. Thus, our results demonstrate that in the absence of predation, intraspecific diversity can affect multiple demographic traits of a foundation species, but the relative importance of these effects depends on the environmental context. Moreover, the magnitude and direction of these effects vary depending on the diversity metric, cohort diversity or genetic relatedness, suggesting that although they are inversely related in this system, each captures sufficiently different components of intraspecific diversity. Given the global loss of oyster reef habitat and rapid decline in oyster population size, our results are particularly relevant to management and restoration. In addition, aquaculture, which commonly excludes predators during early life history stages, may benefit from incorporation of oyster cohort diversity into standard practice.